2016
DOI: 10.1155/2016/4219735
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Activates the APPL1-AMPK-PPARαAxis to Prevent Diabetic Cardiomyocyte Apoptosis

Abstract: Objective. To investigate the effect and mechanism of the exenatide on diabetic cardiomyopathy. Methods. Rats were divided into control group, diabetes group (D), diabetes treated with insulin (DI) group, and diabetes treat with exenatide (DE) group. We detected apoptosis rate by TUNEL, the adiponectin and high molecular weight adiponectin (HMW-adiponectin) by ELISA, and the expression of APPL1, p-AMPK/T-AMPK, PPARα, and NF-κB by immunohistochemistry and western blotting. Results. Compared with the D group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Increased ROS production and reduced antioxidant levels in diabetes have been widely documented in previous reports (Fiordaliso et al., 2004; Houstis et al., 2006). Earlier studies showed that CMs incubated with GLP‐1 or its analogs remained viable and lowered ROS levels and apoptosis rates in both diabetic and nondiabetic models (Inoue et al., 2015; Raab, Vuguin, Stoffers & Simmons, 2009; XiaoTian et al., 2016). Nevertheless, these reports failed to address the possible mechanisms responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS production and reduced antioxidant levels in diabetes have been widely documented in previous reports (Fiordaliso et al., 2004; Houstis et al., 2006). Earlier studies showed that CMs incubated with GLP‐1 or its analogs remained viable and lowered ROS levels and apoptosis rates in both diabetic and nondiabetic models (Inoue et al., 2015; Raab, Vuguin, Stoffers & Simmons, 2009; XiaoTian et al., 2016). Nevertheless, these reports failed to address the possible mechanisms responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Through the recruitment of adaptor protein APPL1 by AdipoRs activation, adiponectin signaling regulates a series of signaling pathways [ 47 ]. AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptor-α (PPARα), IkB kinase (IKK)/NF-κB/PTEN, IRS1/2–Akt, and Ras-ERK1/2 signaling are examples of downstream adiponectin signaling [ 48 , 49 , 50 , 51 , 52 ]. Adiponectin receptors are found to be expressed throughout the whole brain.…”
Section: Adiponectin As a Modulator Of Metabolic Disordermentioning
confidence: 99%
“…The experiment was performed as described previously [ 15 , 17 ]. Deparaffinized sections were incubated with a Par-4 (dilution 1 : 200; Santa Cruz Biotechnology, USA) or TERT (dilution 1 : 200; Santa Cruz Biotechnology, USA) primary antibody overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…TUNEL staining to detect the apoptosis rate and corresponding calculations were performed as previously described [ 15 , 17 ].…”
Section: Methodsmentioning
confidence: 99%